Solubility, porosity, dimensional and volumetric change of endodontic sealers - Torres, Fernanda Ferrari Esteves [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Bosso-Martelo, Roberta; Espir, Camila Galletti [UNESP]; Camilleri, Josette; Tanomaru-Filho, Mario [UNESP] (FapUNIFESP (SciELO), 2019)
The aim Of this study was to evaluate physical properties Of endodontic sealers (AH Plus, MTA Fillapex and Endofill), by conventional and micro-CT tests. Dimensional stability was evaluated after immersion Of materials in distilled water for 30 days. Solubility and volumetric change were evaluated after 7 and 30 days Of immersion in distilled water. Solubility was evaluated by means Of mass loss and volumetric change was assessed by micro-CT. Porosity was evaluated under a microscope after 7 days Of immersion in distilled water, and by using micro-CT after setting and immersion in distilled water for 7 and 30 days. Statistical analysis was performed by ANOVA and Tukey’s test with 5% significance level. MTA Fillapex presented the highest solubility (p<0.05), showing values above the ISO/ADA recommendations. MTA Fillapex presented higher volumetric and dimensional changes, followed by Endofill and AH Plus (p<0.05). Dimensional stability of the MTA Fillapex and AH Plus did not follow ISO/ADA standards. The highest total porosity was Observed for MTA Fillapex (p<0.05). Endofill had higher total porosity than AH Plus according to microscope evaluation (p<0,05), and both sealers were similar in micro-CT assessment (p>0,05). In conclusion, MTA Fillapex presented higher solubility, dimensional and volumetric change besides porosity compared to the Other evaluated sealers. The assessed physical properties of sealers are related, and the different tests provided complementary data. Micro-CT is a valuable method for assessment Of physical properties Of endodontic materials.
Keywords: Endodontics; Physicochemical analysis; Silicate cement; X-ray microtomography